Geographical Indications and Maqāṣid al-Sharī‘ah: Realizing Intellectual Property as an Instrument of Economic Justice - Triyono Adi Saputro; Isman; Diana Setiawati; Azhar Alam; Nur Rizqi Febriandika (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2025)
Intellectual Property (IP) protection in Indonesia remains primarily oriented toward individual and capitalist interests, thereby failing to reflect the values of distributive justice fully. This research aims to analyze Geographical Indications (GIs) as an instrument of economic justice from the perspective of Maqāṣid al-Sharī‘ah. The study employs a normative legal research method, utilizing both conceptual and legislative approaches. Data were gathered through a literature review of primary, secondary, and tertiary legal sources, which were then analyzed qualitatively to examine the relationship between the principles of positive law and the values of Maqāṣid al-Sharī‘ah. The findings indicate that the principles of Maqāṣid al-Sharī‘ah, such as hifz al-mal (protection of property), hifz al-nafs (protection of life), and hifz al-'aql (protection of intellect), provide a strong philosophical foundation for the reconstruction of a just and inclusive IP system. GIs' protection not only provides legal recognition of product origins but also serves as an instrument for the economic empowerment of local communities and the equitable distribution of financial benefits. Incorporating Sharia values into IP policies can broaden the moral, social, and ecological dimensions of a sustainable creative economy. This research recommends reformulating national IP policies by incorporating the principles of Maqāṣid al-Sharī‘ah, strengthening the role of producer communities in GIs governance, and fostering quadruple-helix collaboration among government, academia, industry, and communities. In this way, GIs can serve as an instrument of economic justice and contribute to achieving sustainable development goals.